Anemia situation in two Philippine provinces Implications for the development of an integrated anemia prevention and control programme. - Felix, A. D.; Tuazon, M. A. G.; Africa, L. S.; Collado, R. V. (2003)
A cross sectional study was conducted in the provinces of Eastern Samar and Isabela involving a total of 280 randomly selected children aged 6 - 36 months and 273 non-pregnant, non-lactating women of reproductive age (WRA). Anemia defined as blood Hb below 11.0g/dL among 6 - 36 month old children, and below 12.0g/dL among WRA was found to be a public health concern that needs immediate attention. In Eastern Samar, 40% of the children and 13% of the WRA were anemic. The prevalence was lower in Isabela with 32% among children and 11% among WRA. Iron deficiency was the main predictor of anemia, but all biological factors were correlated with hemoglobin level, indicating multiplicity of causes that requires a mix of interventions and a multi-stakeholder strategic cooperation. The variations across target groups call for group specific integrative approaches.
Keywords: Anemia; Health programs